(untitled) (Colombia Medica, 2011)
Introduction: Type 2 diabetes (DM 2) is one of the first ten causes of mortality in Colombia. Pre-diabetes is a state of hyperglycemia that associated with other risk factors appears 5-10 years before this disease. It has been reported that controlling the diet and exercise decreases the probability of suffering DM 2 by 60%. This intervention requires establishing the risk in pre-diabetic patients. Objectives: To detect patients with pre-diabetes who are members of a private health care provider (EPS for its name in Spanish) in Cali and to describe the clinical and epidemiological characteristics related to the risk of developing DM 2. Materials and methods: This is a cross-sectional descriptive study in patients with altered glucemias (Impaired fasting glucose: 100-125 mg/dl and impaired glucose tolerance: 140-199 mg/dl). Clinical histories were reviewed and surveys on risk factors, habits and perception of knowledge were conducted. We determined: fasting glucose, vital signs, and anthropometric measures. Results: 111 patients were included (64% women) whose most common occupation was home duties (39.6%). The descriptive analysis reported high risk; the results were: noticeable presence of associate pathological antecedents as follows: Diabetes in the family (64%), obesity (54.1%), dyslipidemia (72.1%), and hypertension (66.7%) in a population with a mean age at 51 years and 10.8% were under 40 years of age. This great proportion of overweight or obesity (86.5%), according to BMI, influenced the determination of the high cardio-metabolic risk (81%, agreeing with the WHO). When evaluating diet with consumption frequency, we still found the intake of simple carbohydrates and animal fats; when reviewing physical activity, 53.2% of the patients reported activity in the last 7 days according to the International Physical Activity Questionnaire (IPAQ). Conclusions: 66% of pre-diabetics did not have diagnosis of some disorder of the metabolism of carbohydrates. More than 70% of the patients have high risk of DM 2 with pathological antecedents, inadequate health habits, and low perception of disease complications.